2021
DOI: 10.1007/s40272-021-00481-z
|View full text |Cite
|
Sign up to set email alerts
|

Metamizole Use in Children: Analysis of Drug Utilisation and Adverse Drug Reactions at a German University Hospital between 2015 and 2020

Abstract: Background Metamizole use is controversially discussed due to its potentially serious adverse drug reactions (ADRs). In Germany, however, it remains a popular analgesic and antipyretic drug. Objective The aim of this study was to discuss the safety profile of metamizole in children by analysing the inpatient prescription patterns and presenting the metamizole-related ADRs at a paediatric hospital between 2015 and 2020. Methods Metamizole util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
(42 reference statements)
1
8
0
1
Order By: Relevance
“…Metamizole has been introduced into our clinical practice as a rescue drug because, besides its excellent analgesic properties, it exhibits synergism with non-steroidal anti-inflammatory drugs, paracetamol, and opioids [ 29 ]. To minimize the risk of agranulocytosis, we have used this medicinal product for a short time [ 30 ]. The surveys conducted by Fieler et al [ 31 ] and Witschi et al [ 32 ] confirmed that metamizole is also frequently used by German anesthesiologists in children in the perioperative setting and cases of serious adverse drug reactions such as hemodynamic, anaphylactic, and respiratory reactions (0.3%) or agranulocytosis are very rare (0.14%).…”
Section: Discussionmentioning
confidence: 99%
“…Metamizole has been introduced into our clinical practice as a rescue drug because, besides its excellent analgesic properties, it exhibits synergism with non-steroidal anti-inflammatory drugs, paracetamol, and opioids [ 29 ]. To minimize the risk of agranulocytosis, we have used this medicinal product for a short time [ 30 ]. The surveys conducted by Fieler et al [ 31 ] and Witschi et al [ 32 ] confirmed that metamizole is also frequently used by German anesthesiologists in children in the perioperative setting and cases of serious adverse drug reactions such as hemodynamic, anaphylactic, and respiratory reactions (0.3%) or agranulocytosis are very rare (0.14%).…”
Section: Discussionmentioning
confidence: 99%
“…Metamizole inhibits prostaglandin synthesis, mainly by inhibiting cyclooxygenase 1 (COX-1) and COX-2; moreover, it modulates nociception induced by substance p. Additionally, it affects the cannabinoid system (analgesic and antipyretic action). its spasmolytic action results from inhibition of adenosine reuptake in the CNS and its influence on the cannabinoid system [85][86][87][88][89]. thanks to the relaxing smooth muscle effect, metamizole is particularly useful when pain is accompanied by a spastic component.…”
Section: Metamizole May Be Used For Pain Management In Children -Reco...mentioning
confidence: 99%
“…Additionally, it affects the cannabinoid system (analgesic and antipyretic action). its spasmolytic action results from inhibition of adenosine reuptake in the CNS and its influence on the cannabinoid system [ 85 89 ]. thanks to the relaxing smooth muscle effect, metamizole is particularly useful when pain is accompanied by a spastic component.…”
Section: Pharmacotherapy Of Painmentioning
confidence: 99%
“…В период с июня 2015 по май 2020 г. в рамках системы стимулированной спонтанной отчетности немецкой университетской клиники было зарегистрировано 7 сообщений о случаях НР применения МН у детей, четыре из которых были связаны с агранулоцитозом. В трех из четырех случаев была установлена возможная или более высокая степень причинно-следственной связи [39]. Анкетирование врачей-анестезиологов, имеющих практику ведения пациентов младше 14 лет, показало, что около 50% респондентов использовало МН внутривенно в дозе 15 мг/кг массы тела или ниже, 26% -в дозе от 16 мг/кг до более чем 20 мг/кг.…”
Section: нежелательные реакцииunclassified